Improving overall reliability of radial distribution systems through optimal lateral protection scheme - Tio, Adonis Emmanuel DC. (2011)
Whether the fuse in a distribution feeder is used in a fuse-blow or fuse-save scheme affects the reliability of the power distribution system. Fuse-blow schemes have higher SAIFI, SAIDI, EENS, ASIFI, and ASIDI because temporary faults result in sustained interruptions; fuse-save schemes yields lower SAIFI, SAIDI, EENS, ASIFI, and ASIDI but has increased MAIFIi and MAIFIe. In this project, we developed a reliability optimization program that minimizes a composite reliability index - a weighted sum of the SAIFI, SAIDI, EENS, ASIFI, ASIDI, MAIFIe and the costs of the protective and switching devices. The program determines the optimal number and location of reclosers, switches, and fuses. Moreover, for each fuse in the distribution system, it determines the fuse scheme that should be applied. Current literature optimizes fuse schemes either for an entire distribution system or for an entire group of fuses belonging to a single recloser protection zone. In this paper, we determined the optimal fuse scheme for each fuse individually. The existing binary programming formulations for SAIFI, SAIDI, EENS, ASIFI, and ASIDI do not take into account fuse-save schemes. In this paper, we modified the existing equations to consider fuse-save schemes. To our knowledge, we presented the first binary programming formulation for MAIFIe which considers fuse-save schemes.
Undergraduate student project (B.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric power systems -- Reliability; Electric power distribution -- Reliability